Electrochemical Behaviors for Ag, LSCF and BSCF as Oxygen Electrodes for Proton Conducting IT-SOFC. Issue 10 (1st January 2017) - Sun, Shichen; Cheng, Zhe
Abstract : The electrochemical behaviors of Ag, La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF), and Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) as potential cathodes for proton-conducting intermediate temperature solid oxide fuel cell (IT-SOFC) are studied using symmetrical cells based on a leading proton conducting electrolyte of BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3-δ (BZCYYb) at 450–650°C. The influences of different testing conditions including oxygen and water (H2 O) content as well as cell configuration (i.e., symmetrical cells versus full cells) on the electrochemical behaviors are systematically investigated. It was found that pure LSCF performs rather poorly like Ag and gives very high interfacial resistance, suggesting sluggish electrode reaction and greatly hindered oxide ion transport between LSCF cathode and BZCYYb electrolyte even under dry condition. In comparison, the LSCF-BZCYYb composite and pure BSCF both show much higher activity toward oxygen electrode reaction, and BSCF outperforms the LSCF composite cathode, suggesting BSCF behaves like a mixed oxide ion-electron conductor in dry atmospheres and a mixed proton-electron conductor in humidified atmospheres. The implication of the experimental observations especially in terms of the similarity and differences in electrochemical behaviors between different electrode materials to the overall cathode reaction mechanism for proton conducting IT-SOFC is discussed, and the directions for further improving the cathode performance for proton conducting IT-SOFC are pointed out.